Pengembangan Backend Sistem Informasi Pemasaran Industri Properti Web Pada PT. Total Property - Pradana, Lucky Dwi; Hidayat, Alfin; Utomo, Agus Priyo (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The rapid development of information technology in the digital era has had a significant impact on various aspects of people's lives, including the property industry. However, PT Total Property still uses a conventional approach in its business management, relying on traditional methods and brochure distribution for property information dissemination. This approach poses challenges in operational efficiency and information accessibility for consumers. In response to these challenges, this research aims to develop an API-based backend information system to digitize PT Total Property's business operations. Using the Rapid Application Development (RAD) method with a qualitative case study approach, the research involved interviews and literature study. The development process includes requirements planning, user design, construction, and implementation. As a result, a REST API was successfully developed using the Laravel framework as the backend, improving the efficiency of data management and information access. Blackbox testing shows all functions work well. The REST API is ready to be integrated with the frontend for further development and get wider feedback for future quality and performance improvement.